As condições de vida e saúde de pessoas acima de 50 anos com deficiência e seus cuidadores em um município paulista - Marin, Maria José Sanches; Lorenzetti, Débora; Chacon, Miguel Claudio Moriel [UNESP]; Polo, Mariana Colbachini; Martins, Vinicius Spazzapan; Moreira, Simone Alves Cotrin (Universidade do Estado do Rio Janeiro, 2013)
As disabled people become older, they often have more complex problems, due to the difficulties of social active insertion. This study aims to characterize the socio-demographic and health conditions of people with disabilities aged 50 years and over, and their caregivers. This is a descriptive study conducted through interviews with 43 disabled elderly and 39 caregivers. It was found that people with disabilities live with a relative, 51.2% did not attend formal education, 69.8% survive of retirement, 46.5% used three or more drugs and 69.8% did not do Pap smear / breast or prostate preventive screening. Among caregivers, 79.5% were female, 84.7% have little or no schooling, were sibling or nephew, have been caregivers for ten years or more, do not get help from other relatives and do not have regular leisure activity. Among them, 18% reported three or more health problems and 44% use three or more drugs. Disabled people over 50 exhibit some characteristics similar to other elderly dependents, but their condition of dependency is long lasting, which requires special health actions both for elderly and caregivers.

Pessoas com deficiência, ao se tornarem idosas, muitas vezes apresentam problemas mais complexos, devido às dificuldades de inserção social ativa. Este estudo se propõe a caracterizar as condições sociodemográficas e de saúde de pessoas com deficiência com idade acima de 50 anos, e de seus respectivos cuidadores. Trata-se de estudo descritivo realizado por meio de entrevistas com 43 idosos com deficiência e 39 cuidadores. Constatou-se que as pessoas com deficiência vivem com algum familiar, 51,2% não frequentaram o ensino formal, 69,8% sobrevivem da aposentadoria, 46,5% utilizam três medicamentos ou mais e 69,8% não realizam exame preventivo de câncer de mama/útero ou próstata. Dos cuidadores, 79,5% são do gênero feminino, 84,7% têm pouca ou nenhuma escolaridade, sendo irmão(a) ou sobrinho(a), são cuidadores há dez anos ou mais, não recebem ajuda de outros parentes e não têm atividade regular de lazer. Entre eles, 18% relatam três ou mais problemas de saúde e 44% fazem uso de três ou mais medicamentos. As pessoas acima dos 50 anos, com deficiência, apresentam algumas características semelhantes a outros idosos dependentes, mas sua condição de dependência é de longa duração, o que demanda ações de saúde diferenciadas tanto para esse idoso como para o cuidador.
Health and living conditions of disabled people over 50 years old and their caregivers in a municipality of São Paulo State, Brazil
Keywords: Saúde do Idoso; Pessoas com Deficiência; Visitadores Domiciliares; Relações Profissional-paciente; Cuidadores; Health of the Elderly; Disabled Persons; Home Health Aides; Professional-Patient Relations Caregivers